Average interconnection delay estimation for on-FPGA communication links - Mak,TST; Sedcole,P; Cheung,PYK; Luk,W (Electronics Letters, 2007)
A new method is presented and an analytical expression is derived for average interconnection delay estimation. This method is directly applicable to predicting the average delay for high-bandwidth communication links implemented on FPGAs. The theoretical results are compared with the measured data from the actual circuits and an average error of 4.6% is reported.